Charalampous, Panagiotis - (:unkn) unknown (My University, 2026)
Panagiotis Charalampous is currently a PhD Candidate of the Department of Multimedia & Graphic Arts. He has a diversified scientific background as he holds a BSc in Informatics from the Technological Institute of Athens, an MBA in Management of Engineering and Technology from Northcentral University in Arizona as well as a wealth of professional certifications on various Microsoft Technologies. He has a professional experience in a wide range of software applications and his current research interests evolve around computational acoustics and their applications on virtual reality, interactive environments and video games. Alongside with his PhD studies, he is a senior software engineer at Mediterranean Acoustics R&D, assisting on research and development of innovative software applications in various fields of acoustics.